Efek Inokulasi Konsorsium Mikroba dan Aplikasi Nutrisi terhadap Populasi Azotobacter spp, Serapan N, Pertumbuhan Tanaman dan Hasil Tomat (Solanum lycopersicum L.) pada Sistem Hidroponik - Pujawati Suryatmana; Mahdi Argawan Putra; Nadia Nuraniya Kamaluddin; Mieke Rochimi Setiawati; Betty Natalie Fitriatin; Reginawanti Hindersah (Soilrens, 2021)
Hydroponic system is an alternative agricultural cultivation technology and a potential system to overcome the decreasing availability of land. Tomato production with this system has its own market segment. Balanced nutrient management combined with inoculation of functional microbial consortium (N-fixing bacteria and phosphate solubilizers) is one of the efforts to increase tomato production in a hydroponic system. This experiment aimed to examine the effect of microbial consortium and hydroponic nutrition on tomato plant growth, Azotobacter spp. population, N uptake and tomato yield. The research design used was a factorial randomized block design (RBD) consisted of two factors. The first factor was the dose of the microbial consortium, consisting of three levels (0 mL/polybag, 5 mL/polybag, and 10 mL/polybag. The second factor was the nutritional dose consisting of three levels (0 mL, 250 mL, and 500 mL). The experimental results showed that there was no interaction between the microbial consortium treatment nutrients on hydroponic plants’ height, N uptake, Azotobacter spp. population and tomato yield. Increased nutrient dose significantly increased N uptake, with the highest yield at 500 ml/pot. But the increased nutrients dose did not lead to significantly different tomato yields. Inoculation of the microbial consortium did not significantly increase all tested parameters.